Evaluation of the percutaneous absorption of chlorpromazine from PLO gels across porcine ear and human abdominal skin. (2nd August 2016) - Alsaab, Hashem; Alzhrani, Rami M.; Boddu, Sai H. S.
ABSTRACT: Objective: The overall objective of this work is to determine the percutaneous absorption of chlorpromazine hydrochloride from pluronic lecithin organogels (PLO gels) and verify the suitability of topically applied chlorpromazine hydrochloride PLO gels for use in hospice patients for relieving symptoms such as vomiting and nausea during the end stages of life. Methods: PLO gels of chlorpromazine hydrochloride were prepared using isopropyl palmitate (IPP) or ricinoleic acid (RA) as oil phase. In vitro percutaneous absorption of chlorpromazine hydrochloride was assessed through porcine ear and human abdominal skin. Further, the theoretical steady state plasma concentration (Css ) of chlorpromazine was calculated from the flux values. Results: The pH, viscosity, and stability of both PLO gels prepared with IPP and RA were comparable. The thixotropic property of RA PLO gel was found to be better than that of IPP PLO gel. The permeation of chlorpromazine hydrochloride was higher from RA PLO gel than from IPP PLO gel and pure drug solution. Theoretical Css of chlorpromazine from pure drug solution, IPP PLO gel and RA PLO gel were found to be 1.05, 1.20, and 1.50 ng/ml, respectively. PLO gels only marginally increased the flux and theoretical Css of chlorpromazine. Conclusion: From this study, it is clearly evident that PLO gels fail to achieve required systemic levels of chlorpromazine following topical application. Chlorpromazine PLO gel may not be effective in treating nausea and vomiting for hospice patients with swallowing difficulties.